Dynamic bipedal walking of a dinosaur-like robot with an extant vertebrate's nervous system. Issue 6 (5th December 2013) - Fukuoka, Yasuhiro; Akama, Junki
SUMMARY: In this study, we attempt to develop a biped dinosaur-like walking robot by focusing on its nervous system as well as its mechanism. We developed a robot 'Dinobot' on the basis of palaeontological knowledge on dinosaurs and extant animals. In addition, we employed typical biologically inspired walking gait generation and control methods derived from an extant vertebrate's nervous system. In particular, we utilized a central pattern generator (CPG), which is a locomotion rhythm generator in a vertebrate's spinal cord, to generate the robot's walking rhythm. Moreover, a reflex centre was placed below CPG and it produced joint torque of the legs in the swing and stance phases. Thus, we successfully achieved adaptive 3D dynamic walking generated by the interaction between the original mechanism of dinosaurs and the nervous system of extant animals. Our future goal is to find out a dinosaur's robust locomotive nervous system suitable for its mechanism.